Aeromonas veronii disease in the refined snakehead fish, Ophiocephalus argus (Cantor) - Ferdinard Estrada; Jose V. Marcos; Dolphy Brocka (Advances in Aquaculture and Fisheries Management, 2019)
Aeromonas veronii has been identified as a causative agent of fish and human disease outbreaks. However, there is no definitive data on A. veronii infection in cultured snakehead fish Ophiocephalus argus (Cantor). In this study, a virulent strain S-L was isolated from the farmed snakehead fish suffering from epizootic ulcerative syndrome, and identified as an A. veronii strain using ARIS 2X system. Its taxonomic position was further determined through nucleotide blast search in NCBI website and phylogenetic analysis. The constructed phylogenetic tree using neighbor-joining method further showed that the S-L isolate was the A. veronii strain (GenBank accession no. JQ301790), which was also previously isolated from diseased freshwater fish. In addition, five genes encoding aerolysin, haemolysin, serine protease and two cytotonic enterotoxins were all found present in the S-L isolate which further confirmed its potential virulence. As far as we know, this is the first report of farmed snakehead fish infected with A. veronii